POTENTIAL OF NETWORKING HEALTH AND WELLNESS TOURISM ENTERPRISES FOR SUSTAINABLE DEVELOPMENT - Preeyanart Jeerapattranant; Vuttichat Soonthonsmai; Sakchai Setarnawat (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study aimed to study the potential of health and wellness tourism enterprise integration among entrepreneurs, stakeholders, and integration management that influence the sustainability of health and wellness tourism enterprise network integration in Thailand. This is descriptive research. The sample group consisted of 320 small, medium, and large health and wellness tourism entrepreneurs in Thailand. A questionnaire was used as a tool for data collection. Statistics used included mean, frequency, percentage, standard deviation, and variance. The influence of variables based on the regression model equation was tested by multiple regression analysis with a statistical significance of 0.05. The findings revealed that entrepreneurs have a level of opinion about the potential of entrepreneurs’ health and wellness tourism enterprise integration stakeholders management aspect and community participation are at a high level in all aspects. It was found that the integration potential of entrepreneurs, stakeholders, management and community participation influenced on sustainability of health and wellness tourism enterprise network integration of Thailand.